Penyuluhan Dan Skrining Hipertensi Serta Diabetes Mellitus Dorong Kesadaran Masyarakat Desa Cilengkrang - Akbar Adri Suwendo; Khoerunnisa Khoerunnisa; Ricky Pernando; Silvi Indriani; Adang Sudrazat (CV. SINAR HOWUHOWU, 2026)
Non-communicable diseases (NCDs) such as hypertension and diabetes mellitus pose serious health threats, yet awareness and early detection in rural communities remain low. In Cilengkrang Village, limited access to preventive services leads to underdiagnosed chronic conditions. This community service program aimed to enhance health knowledge and facilitate direct health screening for residents. Using a promotive-preventive approach, the team integrated interactive health education on hypertension and diabetes with a free health screening covering anthropometry, blood pressure, and random blood glucose (RBG) tests for 49 participants. The findings revealed a high prevalence of hypertension at 59.18% (29 participants) and indicated hyperglycemia in 10.20% (5 participants with RBG ≥ 200 mg/dL), with several individuals discovering their conditions for the first time. These results highlight the crucial role of community service programs in early NCD detection. Ultimately, this activity provides a strategic foundation for local village authorities and health personnel to establish routine screenings, train village health cadres, and foster sustainable healthy lifestyle habits.